Penerapan Metode Cosine Similarity Pada Sistem Informasi Retrival Pencarian Terjemahan Ayat-Ayat Suci Al-Qur’An - Poerbaningtyas, Evy; Maulidi, Rakhmad (J-INTECH (Journal of Information and Technology), 2023)
Ayat is a sentence in the Qur'an, the verse is known as tauqifi (with the nash of the Messenger of Allah saw.), not qiasi (analogy). Since it counts (Alif Lam Mim) and (Alif Lam Mim Shod Nun) each as one verse but does not count (Alif Lam Mim) and (Kha Mim), (Alif Lam Mim Ra) and (Ya Syin) each count as one verse, but not so with (Tho Syin Mim), Ayat (Madahaa Mannaan) is one word, according to the agreement, invalid prayer by reading only half of the verse. In a verse some words make up a sentence, so to search for a desired sentence you have to look up 1 by 1 in the verse. Because the guidance of the life of Muslims is the holy book of the Qur'an, in which there are several letters and in the letter there are verses. From these conditions, in this study, a verse search engine was created to facilitate the search process using the cosine similarity method. The purpose of this study is to be able to help the search process quickly and easily, readers in the search for verses in the holy book of the Qur'an .